ANALISIS KESULITAN GURU SEKOLAH DASAR DALAM MELAKSANAKAN AUTHENTIC ASSESSMENT PEMBELAJARAN TEMATIK DI KECAMATAN TEMBALANG - Ratna Nur Oktafiani; Iin Purnamasari; Ari Widyaningrum (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2020)
ABSTRACTThe existence of a policy regarding assessment standards in the 2013 curriculum has resulted in polemics from teachers, especially in terms of authentic assessment of thematic learning. This study aims to analyze the difficulties of elementary school teachers in Tembalang District in carrying out authentic assessment of thematic learning. The research method used in this research is descriptive method with a qualitative approach. Data collection techniques used are through interviews, questionnaires and study documentation. The results showed that the teacher experienced difficulties in carrying out the authentic assessment due to lack of time allocation, inadequate school facilities and infrastructure, the number of assessments inputted, limited mastery of IT, and students who were not supportive. Keywords: Authentic, Assessment, Thematic ABSTRAK              Adanya kebijakan mengenai standar penilaian dikurikulum 2013 menuai polemik dari para guru khususnya segi authentic assessment pembelajaran tematik. Penelitian ini bertujuan untuk menganalisis kesulitan guru sekolah dasar di Kecamatan Tembalang dalam melaksanakan authentic assessment pembelajaran tematik. Metode penelitian yang digunakan pada penelitian ini adalah metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data yang digunakan yaitu melalui wawancara, angket dan study dokomentasi. Hasil penelitian menunjukkan bahwa guru mengalami kesulitan dalam melaksanakan authentic assessment karena kurangnya alokasi waktu, sarana dan prasarana sekolah yang belum memadai, banyaknya penilaian yang diinput, keterbatasan penguasaan IT, dan peserta didik yang kurang mendukung.               Kata kunci: Autentik, Asesmen, Tematik